Strength enhancement of CFRP joints composed of partially unmolded laminates manufactured using Vacuum-Assisted Resin Transfer Molding (VARTM). Issue 3 (17th February 2023) - Abusrea, Mahmoud; Shazly, Mostafa; Terutake, Matsubara; Wen-Xue, Wang; Arakawa, Kazuo
ABSTRACT: Partially unmolded CFRP joints have shown the potential to improve the joining efficiency in adhesive joints. In this work, four different joints were investigated, namely, Original Laminated Joint (OLJ) where the mating parts form butt joints, Overlapped Joints, where mating parts overlapped with different lengths (e.g., 20 mm (O20) and 40 mm (O40)), and a specially designed Multiple-Covers Joint (MLJ). All joints were prepared using the Vacuum-Assisted Resin Transfer Molding (VARTM) process. Tensile and bending specimens were prepared to evaluate the joint's mechanical performance. The O40 achieved the highest ultimate failure load, with a 56% increase over the OLJ specimens. It also achieved the highest bending strength and modulus compared to other joints and even the standard bending samples. The percentage increase in the strength for the proposed joints ranged from 58% to 68% over the OLJ samples. Fractography showed a delamination failure mode for the OLJ and O20 joints, while a mixture of delamination and fiber breakage failure modes was observed for the O40 and MLJ joints. Finite elements modeling (FEM) of the tensile tests were developed. The results showed good agreement with the experimental ones. Furthermore, FEM results clarified some of the experimental observations and the underlying failure mechanisms and damage propagation.